Penanaman Nilai Karakter Gemar Membaca Siswa di SD Negeri Magelang 4 - Vindi Septianingrum; Rasidi Rasidi; Agrissto Bintang Aji Pradana (Universitas Muhammadiyah Magelang, 2023)
This study aims to determine the process of instilling the character value of students' love of reading and the role of school parties, namely principals, teachers, and librarians in instilling the character value of reading, as well as to find out what obstacles are faced in instilling the character value of students' love of reading at SD Negeri Magelang 4 and the solutions provided. The type of research used is qualitative case study research with data collection methods through interviews, observation, and documentation. There are two sources of data in this study including primary data sources, namely principals, teachers, librarians, and students, while secondary data sources are documentation when research is carried out at school. This research uses data triangulation as a data validity test, including source triangulation, technique triangulation, and time triangulation. Furthermore, this research uses data analysis techniques in the form of data collection techniques, data reduction, data presentation, conclusion drawing, and verification. The results showed that 1) schools still need additional facilities to support the continuity of the process of instilling the character value of reading well, 2) principals, teachers, and librarians have played a good role in the process of instilling the character value of reading fond of students such as guiding, directing, and enforcing rules so that students have a character fond of reading, 3) There are still obstacles faced such as students who claim to be lazy to read and there are also several books in the library that can be said to be slightly damaged. However, in addition to obstacles, of course, there are also solutions provided such as adding book collections tailored to the age and reading interests of students at school.